A Cu2+ complex induces the aggregation of human papillomavirus oncoprotein E6 and stabilizes p53. (6th July 2018) - Kumar, Amit; Kuhn, Lars T.; Balbach, Jochen
Abstract : Papillomavirus oncoprotein E6 is a critical factor in the modulation of cervical cancer in humans. At the molecular level, formation of the E6–E6AP‐p53 ternary complex, which directs p53's degradation, is the key instigator of cancer transforming properties. Herein, a Cu 2+ anthracenyl‐terpyridine complex is described which specifically induces the aggregation of E6 in vitro and in cultured cells. For a hijacking mechanism, both E6 and E6AP are required for p53 ubiquitination and degradation. The Cu 2+ complex interacts with E6 at the E6AP and p53 binding sites. We show that E6 function is suppressed by aggregation, rendering it incapable of hijacking p53 and thus increasing its cellular level. Therapeutic treatments of cervical cancer are currently unavailable to infected individuals. We anticipate that this Cu 2+ complex might open up a new therapeutic avenue for the design and development of new chemical entities for the diagnosis and treatment of HPV‐induced cancers. Abstract : Cervical cancer is one of the leading causes of death in women. In humans, papillomavirus oncoprotein E6 is a critical player in inducing cervical cancer and epithelial tumours. We discovered an organic Cu 2+ coordination complex, that, under in vitro conditions, binds with micromolar affinity and induces conformational changes in the target, leading to the self‐association and aggregation of E6. Under in vivo conditions, HPV‐positive HeLa cells exhibited similar types of E6 aggregates upon co‐incubation and a subsequent stabilization of the cellular p53 levels.